quad . eq

Asked by  | 5th Aug, 2008, 03:56: PM

Expert Answer:

 if α ,β   are the  roots of the equation , 

then  sum  of the roots & the products of the roots  of the  equation   X 2 --2X +1 =0    are ,               

                    α  + β  == --2 and αβ == 1

 the required  equation  is  (X  + 2) (X --1 ) ==0  ====> X2   +  X  --2  =0

                                            The equation  whose roots are   --2, 1 is  X2   +X ---  2 ==0

Answered by  | 5th Aug, 2008, 04:39: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.